An Analysis of Teacher Talk in Classroom Interaction at SMPN 15 Padang - Siregar, Fitriyani; Refnaldi, Refnaldi (Journal of English Language Teaching, 2024)
This research analyzes teacher talk spoken in the classroom. From this research, we see what categories are often used in class. The design of this research is descriptive. The subjects of this research are two teachers who teach English classes at SMPN 15 Padang. There are two teachers, a man and a woman who teach the English class. The teachers have more than five years of teaching experience and are certified as school teachers. In this study, researchers focused on teacher talk and the function of teacher talk in classroom interactions in English classes. Researchers obtained data by recording videos of interactions in the classroom. The categories of types of teacher talk contain six categories of teacher talk and there are five categories of teacher talk functions. The research results showed that the six categories of teacher talk appeared 447 times, while the question category appeared the most 165 times. The least used category Criticizing students. The teacher conversation function appeared 142 times with the Instruction category appearing 50 times.